On non-singular crack fields in Helmholtz type enriched elasticity theories. (1st June 2015) - Lazar, Markus; Polyzos, Demosthenes
Highlights: We show that recently proposed non-singular crack fields cannot be fracture mechanics solutions. They do not satisfy the equilibrium equations of nonlocal elasticity and boundary conditions of the problem. They do not satisfy the compatibility equations of gradient elasticity. Abstract: Recently, simple non-singular stress fields of cracks of mode I and mode III have been published by Aifantis (2009, 2011), Isaksson and Hägglund (2013) and Isaksson et al. (2012). In this work we investigate the physical meaning and interpretation of those solutions and if they satisfy important physical conditions (equilibrium, boundary and compatibility conditions).